Efficient Room‐Temperature Phosphorescence from Organic–Inorganic Hybrid Perovskites by Molecular Engineering. Issue 36 (30th July 2018) - Hu, Hongwei; Meier, Fabian; Zhao, Daming; Abe, Yuichiro; Gao, Yang; Chen, Bingbing; Salim, Teddy; Chia, Elbert E. M.; Qiao, Xianfeng; Deibel, Carsten; Lam, Yeng Ming
Abstract: Solution‐processed organic–inorganic hybrid perovskites are promising emitters for next‐generation optoelectronic devices. Multiple‐colored, bright light emission is achieved by tuning their composition and structures. However, there is very little research on exploring optically active organic cations for hybrid perovskites. Here, unique room‐temperature phosphorescence from hybrid perovskites is reported by employing novel organic cations. Efficient room‐temperature phosphorescence is activated by designing a mixed‐cation perovskite system to suppress nonradiative recombination. Multiple‐colored phosphorescence is achieved by molecular design. Moreover, the emission lifetime can be tuned by varying the perovskite composition to achieve persistent luminescence. Efficient room‐temperature phosphorescence is demonstrated in hybrid perovskites that originates from the triplet states of the organic cations, opening a new dimension to the further development of perovskite emitters with novel functional organic cations for versatile display applications. Abstract : Room‐temperature phosphorescence is activated in hybrid perovskites through energy transfer between inorganic and organic layers. By designing a mixed‐cation perovskite system, nonradiative recombination is suppressed for achieving a high phosphorescence efficiency up to 11%. Multiple‐colored emission with millisecond lifetime is achieved. These results emphasize the importance of organic chemistry in further development of perovskite materials for future optoelectronics.